Enrichment of open reading frames presented on bacteriophage M13 using Hyperphage. (September 2006) - Hust, Michael; Meysing, Maren; Schirrmann, Thomas; Selke, Martin; Meens, Jochen; Gerlach, Gerald-F.; Dübel, Stefan
The enrichment of open reading frames (ORFs) from large gene libraries and the presentation of the corresponding polypeptides on filamentous phage M13 (phage display) is frequently used to identify binding partners of unknown ORFs. In particular, phage display is a valuable tool for the identification of pathogen-related antigens and a first step for the development of new diagnostics and therapeutics. Here, we introduce a significant improvement of phage-based ORF enrichment by using Hyperphage, a helperphage with a truncated gIII. The methods allow both the enrichment of ORFs from cDNA libraries and the display of the corresponding polypeptides on phage, thus combining ORF enrichment with a screening for binding in one step without any further subcloning steps. We demonstrated the benefits of the method by isolating the sequences encoding two predicted immunogenic epitopes of the outer membrane protein D encoding gene ( ompD ) of Salmonella typhimurium . Here, we showed that when using a mixture of three constructs with only one containing an ORF, solely this correct construct could be reisolated in phage particles. Further, both epitopes were detected by enzyme-linked immunosorbent assay (ELISA), demonstrating correct translation of fusion proteins. Furthermore, the enrichment system was evaluated by the enrichment of ORFs from total cDNA of lymphocytes. Here, we could show that 60% of the phage contained ORFs, which is an increase of an order of magnitude compared with conventional phage expression system. Together, these data show that the Hyperphage-based enrichment system significantly improves the enrichment of ORFs and directly allows the display of the corresponding polyp eptide on bacteriophage M13.